A comparison of occupational physical activity and sedentary behavior patterns of nurses working 12-h day and night shifts - R.M. Benzo; A. Farag; K.M. Whitaker; Q. Xiao; L.J. Carr (Elsevier, 2021)
Background: Past studies have reported nurses working day shifts engage in high amounts of light and moderate-intensity occupational physical activity. However, little is known regarding how occupational physical activity and sedentary behavior is accumulated within shifts and/or over consecutive shifts. Objective: This study compared occupational physical activity and sedentary behavior patterns of nurses working 12-h. day vs. 12 -h. night shifts. We hypothesized nurses working day shifts would be more active and less sedentary while at work compared to nurses working night shifts and that within shift and between shift differences would emerge. Design: Prospective-cohort study design Setting(s): Midwestern trauma one academic medical center medical units (medical surgical, critical care, pediatrics, mother and baby, and other) Participants: A total of 56 registered nurses working 12-h. day and night shifts participated in this study. Methods: Occupational physical activity and sedentary behaviors (e.g., step count, time spent sitting, standing, and walking) were measured for 14 continuous days using the ActivPAL 3 micro activity monitor. Repeated measures mixed-effects regression models were used to examine the effects of shift type, consecutive shifts, and time within a shift on occupational physical activity and sedentary behaviors. Results: Nurses spent more time standing and walking, and less time sitting overall during day shifts compared to night shifts. Nurses walked less during the third consecutive night shift and stood less and sat more during the second and third consecutive night shifts, compared to day shifts. Nurses tended to walk less and sit more during the middle portion of each night shift compared to day shifts. Conclusions: Our findings suggest nurses spend more than half of each shift either standing or walking and that differential patterns of occupational physical activity and sedentary behavior exist between day and night shifts. These findings should be used to inform future interventions designed to advance the health and work performance of nurses.